2021
DOI: 10.1016/j.euo.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography and Whole-body Magnetic Resonance Imaging for Metastasis-directed Therapy in Hormone-sensitive Oligometastatic Prostate Cancer After Primary Radical Treatment: A Systematic Review

Abstract: Context: Next-generation imaging includes positron emission tomography (PET) imaging and whole-body magnetic resonance imaging (wbMRI) including diffusion-weighted imaging. Accurate quantification of oligometastatic disease using next-generation imaging is important to define the role and value of metastasisdirected therapy (MDT). Objective: To perform a review of next-generation imaging modalities in the detection of recurrent oligometastatic hormone-sensitive prostate cancer in men who received prior radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…8 Moreover, a high level of interobserver agreement was demonstrated for 68 Ga-PSMA PET/ CT, both for nodal and bony lesions. 21,22 Admittedly, PSMA-based techniques may fail to detect clinical progression when PSMA is either absent or scarcely expressed. Although no definitive evidence of superiority of 68 Ga-PSMA PET/CT exists, in the 2017 APCCC, the panelists recommended the use of 68 Ga-PSMA PET/ CT to confirm the diagnosis of oligometastases after primary treatment.…”
Section: Imaging In Ompcmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Moreover, a high level of interobserver agreement was demonstrated for 68 Ga-PSMA PET/ CT, both for nodal and bony lesions. 21,22 Admittedly, PSMA-based techniques may fail to detect clinical progression when PSMA is either absent or scarcely expressed. Although no definitive evidence of superiority of 68 Ga-PSMA PET/CT exists, in the 2017 APCCC, the panelists recommended the use of 68 Ga-PSMA PET/ CT to confirm the diagnosis of oligometastases after primary treatment.…”
Section: Imaging In Ompcmentioning
confidence: 99%
“…28 Finally, in recent years, international guidelines have been published which provide indications for standardising acquisition, interpretation and reporting of WB-MRI. 29 A recent meta-analysis by Farolfi et al, 22 summarizing the strengths and limitations of such NGI modalities, identified PSMA-PET as the most promising modality, with lower inter-observer variability and higher degree of reproducibility. Nevertheless, this study also warns about pitfalls of this technique, such as the possible overestimation of lymph node detection sensitivity, encouraging randomized clinical trials investigating the role of NGI in combination with MDT in this setting.…”
Section: Imaging In Ompcmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, PSMA PET techniques allow visualisation of metastatic disease prior to metastatic deposits, reaching morphological criteria required for diagnosis on conventional imaging (21). Hence, recent trials have evaluated PSMA PETguided MDT in oligometastatic recurrent disease, typically with salvage surgery or radiotherapy, which potentially delays the need for systemic therapy (22)(23)(24). Therefore, we aim to comprehensively review PSMA PET-guided MDT in OMPC.…”
Section: Introductionmentioning
confidence: 99%